Communicable Diseases Intelligence volume 13 issue 22 - 6 November 1989 - whole issue - No author listed (Communicable Diseases Intelligence, 1989)
Whole-issue pdf, comprising: Viruses, Chlamydias, Coxiellas, Rickettsias and Mycoplasmas Reporting Scheme Overseas Brief Dengue fever in Vanuatu and French Polynesia Original article Salmonella surveillance, Australia: non-human isolates, Annual Report, 1988 Update: Aedes Albopictus infestation - United States, Mexico Publication Notice NHMRC Malaria Guidelines for Medical Practitioners Australia - Communicable Diseases Intelligence Period 12/10/1989 to 25/10/1989